As atividades relacionadas ao comércio exterior e desenvolvimento local – um estudo em Porto Xavier, RS - Bellinaso, Pedro Augusto François (2020)
The research aimed to identify the impact of the foreign trade players in the generation of value and development of the Porto Xavier, RS, municipality. The theoretical framework, based on the historical materialism, was elaborated from an ontology of social being centered on labor, which is the founding element of the added value process. The data collection procedures were based on the Analysis-Diagnosis of Agricultural Systems principles. Through interviews, statistical data and the literature on the subject, the historical development of the municipality and the processes of value creation linked to local foreign trade players were studied. The results show that the characteristics of a border municipality are remarkable in the people and history of the municipality of Porto Xavier. The sectors of import and export, international transportation and custom services provision have a relative development in the municipality, with several companies linked to the activities, which are responsible for a substantial part of the municipal added value. It was identified that foreign trade players were important for the development of the municipality, impacting its historical formation process and representing a significant part of the municipality's production and wages. Finally, it was found that the precarious structure of the customs area and the fact that the passage is made by ferries limits the foreign trade players activities development, being the construction of an international bridge, with an adjoining customs area, a possible solution that could be adopted by the government.